2006
DOI: 10.1016/j.jcf.2006.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive prenatal care results in successful fetal outcomes in CF women

Abstract: CF women with severe pulmonary impairment tend to have lower weight babies but it remains difficult to determine prospectively which CF women will tolerate pregnancy well. Aggressive antepartum management is recommended for all CF women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(85 citation statements)
references
References 17 publications
5
69
1
10
Order By: Relevance
“…Among chronic lung diseases, cystic fibrosis (CF) and tuberculosis are the most common conditions: 5% of the world population is carrying the CF gene and 30% of humans have been infected with mycobacterium tuberculosis [55, 56]. Pregnancy in cystic fibrosis patients seems to have a positive effect on maternal long-term survival, despite the increased maternal risk for infections and insulin resistance and the increased fetal risk of prematurity and IUGR [5761]. …”
Section: Intrauterine Hypoxiamentioning
confidence: 99%
“…Among chronic lung diseases, cystic fibrosis (CF) and tuberculosis are the most common conditions: 5% of the world population is carrying the CF gene and 30% of humans have been infected with mycobacterium tuberculosis [55, 56]. Pregnancy in cystic fibrosis patients seems to have a positive effect on maternal long-term survival, despite the increased maternal risk for infections and insulin resistance and the increased fetal risk of prematurity and IUGR [5761]. …”
Section: Intrauterine Hypoxiamentioning
confidence: 99%
“…Concerns have been raised regarding oral contraceptive pill (OCP) usage in CF due to potential malabsorption, and CF liver disease could result in either high serum levels as a consequence of decreased hydroxylated estrogens or decreased serum levels secondary to decreased glucurconide-conjugated estrogens impairing enterohepatic circulation of estrogens [3,4]. There is no difference in sexual practice between CF and age matched females [5] but pregnancy in CF women is associated with increased health care requirements [6,7] The expert opinion of the U.S. CF Foundation Consensus Statement regarding adult care suggests that "issues of female contraception are broadly similar for women with and without CF" [2]. Evidence in support of this assertion, however, is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports and epidemiological studies showed that the A. OVERVIEW OF NUTRITION AND DIETS IN CYSTIC FIBROSIS long-term outcome of women with CF who become pregnant was not worse than that of CF women who did not become pregnant [2,[10][11][12][13][14][15]. Case reports and epidemiological studies showed that the A. OVERVIEW OF NUTRITION AND DIETS IN CYSTIC FIBROSIS long-term outcome of women with CF who become pregnant was not worse than that of CF women who did not become pregnant [2,[10][11][12][13][14][15].…”
Section: Historical Perspectivementioning
confidence: 99%